Research note: exploring the association of work attitudes among Indian police officers - Lambert, Eric G. (Criminal justice studies, 2025)
Job involvement, job satisfaction, and organizational commitment are important work attitudes. Several past studies on police work attitudes have treated the three work attitudes as unrelated concepts. The current study examined the association between these three work attitudes, and it also proposed a path model where job involvement is related to job satisfaction and organizational commitment and job satisfaction is associated with organizational commitment. Further, this study examined two different types of bonds to the organization: continuance commitment (i.e. bonding to the organization to protect investments in the organization) and affective commitment (i.e. bonding to the organization because of positive treatment). Using data from a survey of 827 police officers working in the Haryana State of India, the path model was supported. Job involvement had associations with higher job satisfaction and affective commitment and an association with lower continuance commitment. Job satisfaction had a relationship with lower continuance commitment and a relationship with higher affective commitment.